1976
DOI: 10.1128/aac.10.3.464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Renal Failure and Dialysis on the Serum Concentration of the Aminoglycoside Amikacin

Abstract: Serum and dialysate levels of amikacin were determined at appropriate intervals after a 300-mg intravenous dose as a continuous infusion in six patients with end-stage renal failure undergoing hemodialysis and in three patients on peritoneal dialysis. The mean serum half-life of amikacin was 3.75 h during (or after) hemodialysis and 29 h during (or after) peritoneal dialysis. Although not on hemodialysis in the same six patients, the serum half-life was 28 h. The results indicate that the maintenance dose of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
2

Year Published

1978
1978
1992
1992

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 3 publications
(3 reference statements)
0
6
1
2
Order By: Relevance
“…The high therapeutic ratio achieved with amikacin and noted in our patients (except in the one in whom resist ant P. aeruginosa emerged) obviates the need for an additional dose before dialysis. On the contrary, the relatively low clear ance of amikacin during hemodialysis in our patients (mean post/predialysis levels = 61.5% with a range from 46.2 to 74.0%), and also noted in volunteers [14] indicate that the doses after the initial dose should be decreased. The importance of adjusting doses according to results of readily availa ble results of serum assay determinations for amikacin cannot be overemphasized.…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…The high therapeutic ratio achieved with amikacin and noted in our patients (except in the one in whom resist ant P. aeruginosa emerged) obviates the need for an additional dose before dialysis. On the contrary, the relatively low clear ance of amikacin during hemodialysis in our patients (mean post/predialysis levels = 61.5% with a range from 46.2 to 74.0%), and also noted in volunteers [14] indicate that the doses after the initial dose should be decreased. The importance of adjusting doses according to results of readily availa ble results of serum assay determinations for amikacin cannot be overemphasized.…”
Section: Discussioncontrasting
confidence: 73%
“…They showed that the mean half-life of ami kacin during hemodialysis in Cordis-Dow hollow fiber dialyzers was 3.75 h and recom mended reducing doses after hemodialysis [14]. 4 of our patients maintained thera peutic levels of amikacin with a reduction of dosage administered after hemodialysis.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations